Farnesyltransferase inhibitor R115777 protects against vascular disease in uremic mice - Nikolov, Igor G; Joki, Nobuhiko; Galmiche, Antoine; Nguyen-Khoa, Thao; Guerrera, Ida Chiara; Guillonneau, François; Ivanovski, Ognen; Phan, Olivier; Maizel, Julien; Marçon, Frédéric; Benchitrit, Joyce; Lucas, Anthony; et al. (Elsevier BV, 2013)
Atherosclerosis and vascular calcification are major contributors to cardiovascular morbidity and mortality among chronic kidney disease patients. The mevalonate pathway may play a role in this vascular pathology. Farnesyltransferase inhibitors such as R115777 block one branch of mevalonate pathway. We studied the effects of farnesyltransferase inhibitor R115777 on vascular disease in apolipoprotein E deficient mice with chronic renal failure and on mineral deposition in vitro.